The Concept of the Method for Forecasting the Life Cycle Costs of Technical Objects Supporting the Process of Making Purchasing Decisions - Izabela DZIADUCH (Communications of International Proceedings, 2020)
The level of exploitation costs to be covered by the user of a technical object depends, to a great extent, on the accuracy of the investment decisions made. The selection of the optimal investment decision (i.e. the purchase of a technical object) in terms of how much to invest in order to obtain the highest possible savings over the technical object lifetime should be based on the life cycle cost analysis (LCCA), which covers, e.g., the costs related to an object purchase and its exploitation. The literature on LCC is quite abundant. Articles, monographs, norms and standards present different scopes of this analysis and indicate the industry sectors it is applied in. It should be emphasized, however, that there are still no scientific studies related to LCC estimation considering the variability of exploitation costs of a technical object over time resulting from gradual changes in the object parameters caused by the processes of technical wear, apart from few exceptions. Therefore, the article describes a method aimed at solving the aforementioned problem and becoming a tool facilitating rational purchasing decisions (a buyer will be able to find out the technical object’s estimated life cycle cost at the time of its purchase). The developed method applies econometric modelling, probability distributions and certain elements of descriptive and mathematical statistics. In the method, while estimating cost parameters, the central tendency values and the values of lower and upper quantiles are used, which allows estimating costs in three variants: the expected variant (e.g. modal), the optimistic variant and the pessimistic one.
Keywords: Life cycle cost (LCC); exploitation cost; purchasing decisions.